Profile Implementation Pancasila Students in the Independent Curriculum in Mathematics - Odile Santya Lovanti; Deni Setiawan (Universitas Negeri Semarang, 2023)
Mathematics subjects are considered by most students to be difficult. In the Free Learning Program, students find mathematics easy, because of various innovations from the teachers. The purpose of this study was to analyze the implementation of the Pancasila Student Profile in the Freedom to Learn curriculum in relation to Mathematics Learning. The research method descriptive uses qualitative. The analysis technique consists of data reduction, data presentation, and drawing conclusions. The subjects of this study were school principals, homeroom teachers and students. The selected informants in this study were teachers and principals who understood the profile of Pancasila students. Data validity technique with source triangulation. The results of this study indicate that 1) The planning for the implementation of the Pancasila Student Profile includes training, readiness of documents and completeness of facilities and infrastructure which are all intended for teachers. 2) Implementation of the implementation of the Pancasila Student Profile with planning, implementing, and evaluating learning activities in accordance with teacher competence. 3) Evaluation of implementation is carried out by teachers with school principals and teacher evaluations with students. Constraints in implementation have been made efforts to improve, so that the implementation of the Pancasila Student Profile in Mathematics Learning at Santa Maria Rembang Catholic Elementary School has been carried out properly.